Central role of cardiac fibroblasts in myocardial fibrosis of diabetic cardiomyopathy - Cheng, Yanan; Wang, Yan; Yin, Ruili; Xu, Yongsong; Zhang, Lijie; Zhang, Yuanyuan; Yang, Longyan; Zhao, Dong (Frontiers in Endocrinology, 2023)
Diabetic cardiomyopathy (DCM), a main cardiovascular complication of diabetes, can eventually develop into heart failure and affect the prognosis of patients. Myocardial fibrosis is the main factor causing ventricular wall stiffness and heart failure in DCM. Early control of myocardial fibrosis in DCM is of great significance to prevent or postpone the progression of DCM to heart failure. A growing body of evidence suggests that cardiomyocytes, immunocytes, and endothelial cells involve fibrogenic actions, however, cardiac fibroblasts, the main participants in collagen production, are situated in the most central position in cardiac fibrosis. In this review, we systematically elaborate the source and physiological role of myocardial fibroblasts in the context of DCM, and we also discuss the potential action and mechanism of cardiac fibroblasts in promoting fibrosis, so as to provide guidance for formulating strategies for prevention and treatment of cardiac fibrosis in DCM.